Model behavioral intention melalui tourist destination image dan tourist perceive value - Angga Dewi Anggraeni; Suci Fika Widyana; Ali Mohamad Rezza (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
During the pandemic, Indonesian people were required to live with a new way of life. The purpose of the study was to develop a behavioral intention model of urban tourists in visiting Health Spa tourism during the adaptation period of new habits in West Java. Factors in the study include tourist emotions, tourist perception values, and image of tourist destinations. The goal is set based on the problem of knowing the factors that influence the behavioral intentions of tourists in the era of adapting new habits. The data collection method is in the form of a questionnaire. The data processing method uses simple data analysis using SPSS and the Structure Equation Model (SEM) method on objects related to the factors that influence behavior in the era of adapting new habits. The results of the study found that tourist emotions had a positive and significant influence on behavioral intentions, but the image of tourist destinations was not able to be a mediating variable between tourist emotions and behavioral intentions. Tourist emotions have a positive and significant influence on behavioral intentions through the image of tourist destinations and the value of tourist perceptions.